Bench Validation of a Compact Low-Flow CO2 Removal Device - Alexandra G. May; R. Garrett Jeffries; Brian J. Frankowski; Greg W. Burgreen; William J. Federspiel (Intensive Care Medicine Experimental, 2018)
Abstract Background There is increasing evidence demonstrating the value of partial extracorporeal CO2 removal (ECCO2R) for the treatment of hypercapnia in patients with acute exacerbations of chronic obstructive pulmonary disease and acute respiratory distress syndrome. Mechanical ventilation has traditionally been used to treat hypercapnia in these patients, however, it has been well-established that aggressive ventilator settings can lead to ventilator-induced lung injury. ECCO2R removes CO2 independently of the lungs and has been used to permit lung protective ventilation to prevent ventilator-induced lung injury, prevent intubation, and aid in ventilator weaning. The Low-Flow Pittsburgh Ambulatory Lung (LF-PAL) is a low-flow ECCO2R device that integrates the fiber bundle (0.65 m2) and centrifugal pump into a compact unit to permit patient ambulation. Methods A blood analog was used to evaluate the performance of the pump at various impeller rotation rates. In vitro CO2 removal tested under normocapnic conditions and 6-h hemolysis testing were completed using bovine blood. Computational fluid dynamics and a mass-transfer model were also used to evaluate the performance of the LF-PAL. Results The integrated pump was able to generate flows up to 700 mL/min against the Hemolung 15.5 Fr dual lumen catheter. The maximum vCO2 of 105 mL/min was achieved at a blood flow rate of 700 mL/min. The therapeutic index of hemolysis was 0.080 g/(100 min). The normalized index of hemolysis was 0.158 g/(100 L). Conclusions The LF-PAL met pumping, CO2 removal, and hemolysis design targets and has the potential to enable ambulation while on ECCO2R.